Analisis Komparatif Kinerja Pemasaran Sebelum dan Sesudah Implementasi Digital Marketing pada Usaha Kuliner di Kecamatan Medan Sunggal - Sihotang, Cristint; Salqaura, Siti Alhamra; Siregar, Muhammad Yamin (Journal of Innovative and Creativity, 2026)
This study aims to analyze the difference in sales performance before and after the implementation of digital marketing at MIEGO CRIS Trading Business in Medan Sunggal. Digital marketing was implemented as an effort to expand marketing reach and increase product sales. The research used a quantitative method with a comparative approach. Data were obtained from sales reports before and after the implementation of digital marketing, as well as questionnaires distributed to customers. The data analysis technique used was the Wilcoxon Signed Rank Test. The sample consisted of 30 respondents, who were the same individuals in both the before and after conditions of digital marketing implementation. The test was conducted using the Wilcoxon Signed Rank Test to determine the difference between the conditions before and after the implementation of digital marketing. The results showed a significant difference between the conditions before and after the implementation of digital marketing during the 2023–2025 period, with a Z value of –3.490 and a significance value of 0.000 (Asymp. Sig. 2-tailed). It can therefore be concluded that the implementation of digital marketing has a significant influence on improving the sales performance of Usaha Dagang MIEGO CRIS in Medan Sunggal.